Price Discrimination by a Many-Product Firm - Armstrong, Mark (Review of Economic Studies, 1999)
Determining the optimal selling strategy for a multiproduct firm facing consumers with unobservable tastes is a difficult task. This paper aims to show how almost optimal nonlinear tariffs can often be found when the number of products is large. Moreover, such tariffs take a simple form: (i) when taste parameters are independently distributed across products, the almost optimal tariff is a single cost-based two-part tariff which can extract virtually all consumer surplus; (ii) when tastes are correlated across products, perhaps because of income differences across consumers, the almost optimal tariff can be implemented as a menu of two-part tariffs each of which has prices proportional to marginal costs.